2013
DOI: 10.1111/nure.12044
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of genistein in metabolic, inflammatory, and malignant diseases

Abstract: Genistein is a soy-derived biologically active isoflavone that exhibits diverse health-promoting effects. An increasing body of evidence shows that genistein influences lipid homeostasis and insulin resistance, counteracts inflammatory cytokines, and possesses antidiabetic properties. Genistein also impedes cancer progression by promoting apoptosis, inducing cell cycle arrest, modulating intracellular signaling pathways, and inhibiting angiogenesis and metastasis of neoplastic cells. This review summarizes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 143 publications
1
36
0
Order By: Relevance
“…Soy isoflavonoids also exhibit anti-angiogenic activities, but the precise mechanism of inhibition remains unclear. These compounds exert anti-angiogenic effect either directly through endothelial cells (EC) or indirectly by modulating the tumor microenvironment [79,80,81]. …”
Section: Antiangiogenic Effect Of Soy Isoflavonoidsmentioning
confidence: 99%
“…Soy isoflavonoids also exhibit anti-angiogenic activities, but the precise mechanism of inhibition remains unclear. These compounds exert anti-angiogenic effect either directly through endothelial cells (EC) or indirectly by modulating the tumor microenvironment [79,80,81]. …”
Section: Antiangiogenic Effect Of Soy Isoflavonoidsmentioning
confidence: 99%
“…Interestingly, several desmosomal genes have recently been linked to tumor suppressive activity (Chun and Hanahan, 2010, Dusek and Attardi, 2011), with the onset of cancer progression through methylation of desmosomal genes (Cui, et al, 2012a, Cui, et al, 2012b). Genistein has been shown to have anti-cancer effects through the inhibition of tyrosine kinases and the modulation of related cellular pathways (Mahmoud, et al, 2014, Nagaraju, et al, 2013). It is interesting to speculate that perhaps one of the many ways in which genistein acts to impede cancer progression is by affecting desmosomal adhesion through pathways similar to its protective effects in pemphigus models.…”
Section: Acquired Desmosomal Diseasesmentioning
confidence: 99%
“…Gen has multiple biological functions such as regulating lipid homeostasis and insulin resistance, counteracting inflammatory response, impeding cancer progression, alleviating Alzheimer's disease, and so on [17]. Accumulating evidence has shown that Gen can improve heart and blood vessel function and prevent cardiovascular diseases [18,19].…”
Section: Introductionmentioning
confidence: 99%